Protective effects of garlic extract on cardiac function, heart rate variability, and cardiac mitochondria in obese insulin-resistant rats - Supakul L. (D. Steinkopff-Verlag, 2015)
PURPOSE: Garlic has been shown to exhibit antioxidant effects and cardioprotective properties. However, the effects of garlic extract on the heart in insulin resistance induced by long-term high-fat-diet consumption are not well defined. Therefore, we sought to determine the effects of garlic extract in the obese insulin-resistant rats. METHODS: Male Wistar rats (180-200 g) were divided into two groups: normal-diet or high-fat-diet (n = 24/group) fed for 12 weeks. Rats in each groups were divided into three subgroups (n = 8 each): vehicle or garlic extract (250 or 500 mg/kg/day, respectively) treated for 28 days. At the end of the treatment, the metabolic parameters, heart rate variability (HRV), cardiac function, and cardiac mitochondrial function were determined. RESULTS: Rats that received a high-fat-diet for 12 weeks had increased body weight, visceral fat, plasma insulin levels, total cholesterol, oxidative stress levels, depressed HRV, and cardiac mitochondrial dysfunction. Garlic extract at both concentrations significantly decreased the plasma insulin, total cholesterol, homeostasis model assessment index, and oxidative stress levels. Furthermore, garlic extract at both doses restored the HRV, cardiac function, and cardiac mitochondrial function. CONCLUSION: We concluded that garlic extract at both concentrations exerted cardioprotective effects against cardiac dysfunction and mitochondrial dysfunction in obese insulin-resistant rats.